Pengaruh Model Problem-Based Learning berbantu Media Problem Card terhadap Hasil Belajar Kognitif dan Sikap Peduli TNWK - Fika Ambarwaty; Arwin Surbakti; Nadya Meriza (Universitas Lampung, 2022)
The research aimed to know the effect of Problem-Based Learning model supported by problem card media on cognitive learning outcomes and environmental care attitude of the TNWK by students of SMPN 1 Labuhan Ratu. The research design used in this study is the non-equivalent control group design. The research took sample of 60 students consisting of class VII 5 as a control class and VII 6 as an experimental class with cluster random sampling technique. The type of data in this research is quantitative data in the form of score on students’ cognitive learning outcomes and environmental care attitude of the TNWK. The data were obtained from environmental pollution questions and attitude questionnaires were analysed using the Independent Sample T-test. The results showed that at the 5% significance level, the Sig. score was obtained (2-tailed) 0,0000,05 for cognitive learning outcomes and 0,0040,05 for environmental care attitude. So it can be concluded that there is a significant effect of Problem-Based Learning model supported by problem card media on cognitive learning outcomes and environmental care attitude of the TNWK.Penelitian ini bertujuan untuk megetahui pengaruh model Problem-Based Learning berbantu media problem card terhadap hasil belajar kognitif dan sikap peduli TNWK peserta didik SMPN 1 Labuhan Ratu. Desain penelitian yang digunakan dalam penelitian ini adalah non-equivalent control group design. Sampel penelitian berjumlah 60 peserta didik yang terdiri dari kelas VII 5 sebagai kelas kontrol dan VII 6 sebagai kelas eksperimen dengan teknik pengambilan sampel cluster radom sampling. Jenis data dalam penelitian ini yaitu kuantitatif berupa nilai hasil belajar kognitif dan nilai sikap peduli TNWK. Data diperoleh dari tes materi pencemaran lingkungan dan angket sikap yang dianalisis secara statistik menggunakan uji Independent Sample T-test. Hasil penelitian menunjukan bahwa pada taraf signifikasi 5% didapatkan nilai Sig. (2-tailed) 0,0000,05 untuk hasil belajar kognitif dan 0,0040,05 untuk sikap peduli TNWK. Sehingga dapat disimpulkan terdapat pengaruh yang signifikan penerapan model Problem-Based Learning berbantu media Problem card terhadap hasil belajar kognitif dan sikap peduli TNWK.Kata kunci: hasil belajar kognitif, problem-based learning, problem card, sikap peduli DOI: http://dx.doi.org/10.23960/jbt.v10i2.25331